Effectiveness of Progressive Muscle Relaxation for Adults with Non-Specific Neck Pain: A Systematic Review - Sugino, Lainun Shabrina; Santoso, Iman (Majalah Ilmiah Fisioterapi Indonesia; Vol 13 No 2 (2025): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/mifi.2025.v13.i02.p20, 2025)
Background : Non-specific neck pain is a prevalent musculoskeletal disorder in adults, often associated with prolonged static posture and psychological stress. This condition can impair daily activities, productivity, and quality of life. Progressive Muscle Relaxation (PMR) has been proposed as a non-pharmacological intervention to reduce symptoms and improve function. Methods : This systematic review followed PRISMA guidelines. A comprehensive search was conducted in PubMed, Semantic Scholar, and Google Scholar, identifying 642 articles. Five studies published between 2015 and 2025 met the inclusion criteria: randomized controlled trials or quasi-experimental designs involving adults aged 15–60 years diagnosed with non-specific neck pain, evaluating the effects of PMR on functional outcomes. Keywords used included (“Progressive Muscle Relaxation” OR “PMR”) AND (“Neck Pain” OR “Nonspecific Neck Pain”) AND (“Function” OR “Disability”). Methodological quality was assessed using the PEDro scale, and data were narratively synthesized due to heterogeneity in study designs and outcome measures. Results : All five studies reported that PMR effectively reduced pain intensity and muscle tension while improving neck function. PEDro scores ranged from 5 to 6, indicating moderate to good quality. Several studies noted additional benefits when PMR was combined with exercise or educational interventions. Conclusion : PMR is a safe, accessible, and cost-effective intervention that can improve functional outcomes in adults with non-specific neck pain, as measured by tools such as the Neck Disability Index. Further high-quality studies with standardized protocols are needed to strengthen current evidence. Keywords : Progressive Muscle Relaxation, Neck Pain, Adults